Diagnosis and screening of patients with hereditary angioedema in primary care - Henao MP; Kraschnewski JL; Kelbel T; Craig TJ (Dove Medical Press, 2016)
Maria Paula Henao,1 Jennifer L Kraschnewski,1 Theodore Kelbel,2 Timothy J Craig3 1Department of Medicine, 2Division of Allergy and Immunology, 3Department of Medicine and Pediatrics, Pennsylvania State University College of Medicine at Hershey Medical Center, Hershey, PA, USA Abstract: Hereditary angioedema (HAE) is a rare autosomal dominant disease that commonly manifests with episodes of cutaneous or submucosal angioedema and intense abdominal pain. The condition usually presents due to a deficiency of C1 esterase inhibitor (C1-INH) that leads to the overproduction of bradykinin, causing an abrupt increase in vascular permeability. A less-understood and less-common form of the disease presents with normal C1-INH levels. Symptoms of angioedema may be confused initially with mast cell-mediated angioedema, such as allergic reactions, and may perplex physicians when epinephrine, antihistamine, or glucocorticoid therapies do not provide relief. Similarly, abdominal attacks may lead to unnecessary surgeries or opiate dependence. All affected individuals are at risk for a life-threatening episode of laryngeal angioedema, which continues to be a source of fatalities due to asphyxiation. Unfortunately, the diagnosis is delayed on average by almost a decade due to a misunderstanding of symptoms and general lack of awareness of the disease. Once physicians suspect HAE, however, diagnostic methods are reliable and available at most laboratories, and include testing for C4, C1-INH protein, and C1-INH functional levels. In patients with HAE, management consists of acute treatment of an attack as well as possible short- or long-term prophylaxis. Plasma-derived C1-INH, ecallantide, icatibant, and recombinant human C1-INH are new treatments that have been shown to be safe and effective in the treatment of HAE attacks. The current understanding of HAE has greatly improved in recent decades, leading to growing awareness, new treatments, improved management strategies, and better outcomes for patients. Keywords: hereditary angioedema, HAE, C1-INH, C1-INH deficiency, angioedema, abdominal pain